Ceftaroline versus vancomycin in the treatment of methicillin-resistant Staphylococcus aureus (MRSA) in an experimental MRSA meningitis model. (September 2020) - Mermer, Sinan; Turhan, Tuncer; Bolat, Elif; Aydemir, Sohret; Yamazhan, Tansu; Pullukcu, Husnu; Arda, Bilgin; Sipahi, Hilal; Ulusoy, Sercan; Sipahi, Oguz Resat
Highlights: MRSA is an important cause of nosocomial meningitis, with limited treatment options. Limited data exist on ceftaroline, for therapy of meningitis. Herein, we compared ceftaroline with vancomycin in an experimental rabbit model. Ceftaroline and vancomycin had similar activity for experimental MRSA meningitis. Abstract: Objectives: The aim of this study was to compare the antibacterial activity of ceftaroline versus vancomycin in the treatment of methicillin-resistant Staphylococcus aureus (MRSA) meningitis in an experimental rabbit meningitis model. Methods: The antibacterial activity of ceftaroline was compared with vancomycin in the treatment of meningitis induced by MRSA strain ATCC 43300 in an experimental rabbit meningitis model. Quantitative cerebrospinal fluid (CSF) cultures were performed at the beginning of antibiotic treatment and 24 h and 73 h after the first antibiotic dose. Furthermore, in vitro time–kill data were investigated at 0, 2, 4, 6, 8, 12 and 24 h in sterile human serum. Results: The difference between the control group versus both treatment groups was significant when comparing the decrease in colony counts in CSF both at 24 h and 73 h after the first antibiotic dose ( P  < 0.05). At the end of the experiment, there was a significant difference in survival between both the ceftaroline-treated group and the vancomycin-treated group versus the control group, but not between the two treatment groups. Conclusion: These results suggest that the antibacterial activity of both ceftaroline and vancomycin are similar in the treatment of MRSA meningitis in an experimental rabbit meningitis model.